Outsourcing procesów logistycznych jako czynnik kreowania wartości w zintegrowanym łańcuchu dostaw - Piechota, Robert (Outsourcing of logistic processes as a factor of customer value creation and rationalization of costs in the integrated supply chain, 2006)
Today many markets are organized in the form of networks of different companies. The companies to compete successfully try to gain mutual target which is customer value. If they succeed they reach the effects such as additional synergy effects and competitive advantage. To do it, however, companies must create and use in practice some basic rules. In this article the author concentrates on some chosen rules that should drive partner relationships within the network.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 345-355